Evaluation of Coffee Pulp Waste from Coffee Cultivation Areas in Indonesia as Iron Booster - Setyobudi, Roy Hendroko; Atoum, Manar Fayiz Mousa; Damat, Damat; Yandri, Erkata; Nugroho, Yogo Adi; Susanti, Mardiana Sri; Wahono, Satriyo Krido; Widodo, Wahyu; Zalizar, Lili; Wahyudi, Ahmad; Saati, Elfi Anis; Maftuchah, M.; et al. (Hashemite University, 2022)
The research aimed to reduce the amount of coffee pulp (CP) as a pollutant and turn it into Coffee Cherry Fluor (CCF) as a functional food. CCF is expected to serve a function as a non-heme iron source to treat anemia. Further, reusing CP should be able to boost the circulation of economy. Six CP samples from three Arabica coffee areas (highlands of Mount Batur, Mount Ijen, and Mount Arjuno) in Indonesia were compared to La Boite CCF, a commercial product made in Brazil. Variables observed were iron contents which is determined by Inductively Coupled Plasma Optical Emission Spectrometer, vitamin C contents as enhancers by Iodimetric titration, total phenol contents as inhibitors by Folin-Ciocalteu method, tannin contents by spectrophotometry method, lignin contents by Van Soest method, total plant count by ISO 4833-1, and antioxidant capacity by IC 50 in the DPPH scavenging assay. Sample disparity significance was statistically determined by ANOVA, followed by Tukey test at 95 %. Sample resemblance with La Boite CCF was tested using Principal Coordinates Analysis (PCoA) and then presented in Heat Map. Conclusively, Mengani CCF and Mengani CP Estate samples are similar to La Boite CCF regarding vitamin C and inhibitor contents. It is suggested to reduce the temperature of the artificial drying device in Mengani. Further research should cover heavy metal contents, proximate analysis, and the detail of amino acid contents as research observed variables; expanding this research in vivo to study non-heme Fe's bioavailability should also be conducted.